Improved treatment outcomes with bedaquiline when substituted for second-line injectable agents in multidrug-resistant tuberculosis: A retrospective cohort study - Zhao, Ying (Department of Medicine, 2020)
Background Bedaquiline is used as a substitute for second-line injectable (SLI) intolerance in the treatment of multidrug-resistant tuberculosis (MDR-TB), but the efficacy and safety of this strategy is unknown. Methods We performed a retrospective cohort study to evaluate treatment outcomes for MDR-TB patients who substituted bedaquiline for SLIs. Adults receiving bedaquiline substitution for MDR-TB therapy, plus a matched control group who did not receive bedaquiline, were identified from the electronic TB register in the Western Cape Province, South Africa. The primary outcome measure was the proportion of patients with death, loss to follow up, or failure to achieve sustained culture conversion at 12 months of treatment. Results Data from 162 patients who received bedaquiline substitution and 168 controls were analyzed; 70.6% were HIV-infected. Unfavorable outcomes occurred in 35/146 (23.9%) patients in the bedaquiline group versus 51/141 (36.2%) in the control group (relative risk, 0.66; 95% confidence interval [CI], 0.46 to 0.95). The number of patients with culture reversion was lower in those receiving bedaquiline (1 patient, 0.8%) compared to controls (12 patients, 10.3%; P = 0.001). Delayed initiation of bedaquiline was independently associated with failure to achieve sustained culture conversion (adjusted odds ratio, 1.5; 95% CI, 1.1 – 1.9, for every 30-day delay). Mortality was similar at 12 months (11 deaths in each group; P = 0.973). Conclusions Substituting bedaquiline for SLIs in MDR-TB treatment resulted in improved outcomes at 12 months compared with patients who remained on SLIs, supporting the use of bedaquiline for MDR-TB treatment in programmatic settings.